Proteomic and metabolic traits of grape exocarp to explain different anthocyanin concentrations of the cultivars - Negri, Alfredo S.; Prinsi, Bhakti; Failla, Osvaldo; Scienza, Attilio; Espen, Luca (Frontiers in Plant Science, 2015)
The role of grape berry skin as a protective barrier against damage by physical injuries and pathogen attacks requires a metabolism able to sustain biosynthetic activities such as those relating to secondary compounds (i.e. flavonoids). In order to draw the attention on these biochemical processes, a proteomic and metabolomic comparative analysis was performed among Riesling Italico, Pinot Gris, Pinot Noir and Croatina cultivars, which are known to accumulate anthocyanins to a different extent. The application of multivariate statistics on the dataset pointed out that the cultivars were distinguishable from each other and the order in which they were grouped mainly reflected their relative anthocyanin contents. Sorting the spots according to their significance 100 proteins were characterized by LC-ESI-MS/MS. Through GC-MS, performed in Selected Ion Monitoring (SIM) mode, 57 primary metabolites were analyzed and the differences in abundance of 16 of them resulted statically significant to ANOVA test. Considering the functional distribution, the identified proteins were involved in many physiological processes such as stress, defense, carbon metabolism, energy conversion and secondary metabolism. The trends of some metabolites were related to those of the protein data. Taken together, the results permitted to highlight the relationships between the secondary compound pathways and the main metabolism (e.g. glycolysis and TCA cycle). Moreover, the trend of accumulation of many proteins involved in stress responses, reinforced the idea that they could play a role in the cultivar specific developmental plan.